Virulence genes and antibiotic resistance assessment of the blaCTX-M-15 gene in ESBL-producing Escherichia coli and Klebsiella pneumoniae from poultry food chain and human clinical cases in Brazil - Pereira, Natália [UNESP]; Cardozo, Marita Vedovelli; Guastalli, Elisabete Aparecida Lopes; dos Santos, Luis Fernando; Valmorbida, Mylena Karoline [UNESP]; Pizauro, Lucas José Luduvério [UNESP]; de Almeida, Camila Chioda [UNESP]; Bragança, Caio Roberto Soares; de Ávila, Fernando Antônio [UNESP] (Universidade Estadual de Londrina, 2023)
Brazil is one of the world’s largest exporters of chicken-derived products. Consumer concerns regarding food contamination by multidrug-resistant bacteria capable of causing diseases have increased steadily over the years as they pose a significant public health risk. This study aimed to characterize strains of beta-lactam-resistant Escherichia coli and Klebsiella pneumoniae isolates from the poultry production chain and human clinical samples (chicken cloaca, chicken meat, human feces). A total of 36 isolates were examined, including 28 Escherichia coli and 8 Klebsiella pneumoniae isolates carrying the blaCTX-M-15 gene. These isolates were obtained from chicken cloaca and meat from poultry farms and slaughterhouses, respectively, as well as from human fecal samples from a clinical laboratory. All the establishments were located in São Paulo, Brazil. The isolates were characterized for their virulence genes by polymerase chain reaction, antimicrobial resistance by the disc diffusion method, serotyping by an agglutination test, and pathogenicity by an in vivo day-old chicken mortality test. The isolates exhibited a high frequency of Escherichia coli associated virulence genes such as iutA, iss, hlyF, ompT and iroN. In addition, mrkD was detected in the isolates. All isolates exhibited resistance to at least three different antimicrobial classes, and 21.4% (n = 6) of the Escherichia coli strains exhibited high pathogenicity in the day-old chicken assay in vivo. These results indicate a potential increase in the blaCTX-M-15 gene associated with virulence genes and antimicrobial resistance in Escherichia coli and Klebsiella pneumoniae. Both of these Enterobacteriaceae can be found in poultry feces and possibly contaminate poultry products, thus posing a risk of infection to other animals and humans, raising an alert about the sanitary aspects of food production in Brazil.
Avaliação de genes de virulência e resistência a antimicrobianos em Escherichia coli e Klebsiella pneumoniae produtoras de beta-lactamase de espectro estendido na cadeia produtiva avícola e em fezes humanas no Brasil
Keywords: Avian pathogenic Escherichia coli; Foodborne disease; Klebsiella pneumoniae; Poultry; Public health; Virulence genes